Analysis of the Development Needs for AI-Based Electronic Arabic Teaching Materials - Salim, Irfan; Elfizawati, Elfizawati; Jannah, Roudhotul; Khaeroni, Khaeroni (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2024)
Educators and instructors need to prepare various elements necessary for developing teaching materials by incorporating AI to create engaging, effective, and efficient learning. This research aims to describe the requirements in developing AI-based teaching materials that align with the needs of students and the instructional approaches utilized. The subjects involved in this study are students from the Faculty of Education and Arabic Language lecturers. A qualitative approach is employed to describe the research objectives. The study reveals that students' understanding of Arabic language learning falls within the moderate category; instructors develop AI-based teaching materials to assist students in comprehending the subject matter, concretizing abstract concepts, supplementing reading materials or references, creating an engaging learning environment, and enhancing interaction during the learning process. Constraints in implementing AI-based teaching materials can be categorized into physical and non-physical resources; however, the supporting facilities and infrastructure for implementing AI-based teaching materials are deemed sufficient.